Comprehensive assessment of metabolic syndrome among rural Bangladeshi women - Jesmin Subrina; Islam Md; Islam A M; Mia Md; Sultana Sayeeda; Zaedi Sohel; Yamaguchi Naoto; Iwashima Yoshio; Hiroe Michiaki; Watanabe Tetsu (BMC, 2012)
Abstract Background Metabolic syndrome (MS), defined as a constellation of cardiovascular disease (CVD) risk factors, is one of the fastest growing public health burdens in the Asia-Pacific region. This trend is despite the fact that people in this region are no more overweight than Europeans and Americans. Unfortunately, in South Asia, MS screening has only been performed in a few countries other than Bangladesh. Therefore the present study is designed to conduct a comprehensive screening of MS in Bangladeshi rural women, which includes estimation of prevalence and assessment of risk factor. Methods A total of 1535 rural Bangladesh women aged ≥ 15 years were studied using a population based cross-sectional survey. The prevalence of MS was estimated using NCEP ATP III, modified NCEP ATP III and IDF criteria. Results The prevalence rates of MS were 25.60% (NCEP ATP III), 36.68% (modified NCEP ATP III), and 19.80% (IDF), as revealed by the present study. Furthermore, based on the NCEP ATP III criteria, 11.60% of the subjects were found to have excess waist circumference; 29.12% had elevated blood pressure, 30.42% had elevated fasting plasma glucose level, 85.47% had low HDL values and 26.91% had increased triglyceride values. Low plasma HDL level was found to be the most common abnormality in the target population and elevated waist circumference was the least frequent component. Conclusions The present study reveals a high prevalence of MS and its associated risk factors in rural Bangladeshi women. These findings are important in that they provide insights that will be helpful in formulating effective public health policy, notably the development of future health prevention strategies in Bangladesh.